Web-based system for processing medical research data - Topuzov, Edem; Ampilova, Natalia (Computer Tools in Education, 2024)
The issues associated with processing of large amount of medical data are discussed in the article. The limitations of using existing medical information systems in individual research are noted. To simplify medical research processes, web-based system has been developed. The system introduces such features as research design, collaboration, data input, access control, audit of database changes, regular backup, data analysis, and exporting data as sheets and plots. The designed system was deployed to production and received positive feedback from users. The certificate of state registration of a computer program was obtained.